2016
DOI: 10.1136/bmjopen-2015-011012
|View full text |Cite
|
Sign up to set email alerts
|

Patient attitudes about the clinical use of placebo: qualitative perspectives from a telephone survey

Abstract: ObjectivesTo examine qualitative responses regarding the use of placebo treatments in medical care in a sample of US patients.Survey studies suggest a deliberate clinical use of placebos by physicians, and prior research has found that although most US patients find placebo use acceptable, the rationale for these beliefs is largely unknown.SettingMembers of the Outpatient Clinic at the Kaiser Permanente Northern California interviewed research participants who had been seen for a chronic health problem at leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…There is a critical need for educating clinicians and patients about the nature of detrimental effects of nocebo processes, including how, when, and why they happen. It has been shown that patients welcome the possibility of being informed about the placebo phenomenon (Ortiz, Hull, and Colloca 2016). Likewise, educating patients about nocebo effects, the experience of other patients will help understand and contextualize the potential for anxiety and other psychophysiological mechanisms that could lead to the occurrence of unwanted nocebo effects.…”
mentioning
confidence: 99%
“…There is a critical need for educating clinicians and patients about the nature of detrimental effects of nocebo processes, including how, when, and why they happen. It has been shown that patients welcome the possibility of being informed about the placebo phenomenon (Ortiz, Hull, and Colloca 2016). Likewise, educating patients about nocebo effects, the experience of other patients will help understand and contextualize the potential for anxiety and other psychophysiological mechanisms that could lead to the occurrence of unwanted nocebo effects.…”
mentioning
confidence: 99%
“…OLP, on the other hand, is accompanied by informed consent and transparency, which seems to solve the ethical controversy of placebo use . Moreover, the acceptance of OLP regimens by patients appears to be high, as 85% of surveyed patients felt it was acceptable for a physician to use a placebo …”
Section: Mechanisms Of the Placebo Responsementioning
confidence: 99%
“…86 Moreover, the acceptance of OLP regimens by patients appears to be high, as 85% of surveyed patients felt it was acceptable for a physician to use a placebo. 87 Regardless of the advantages of OLP, the aforementioned trials pose some limitations. These include small sample size, heterogeneity of medical conditions studied, and lack of long-term follow-up to examine long-term effects of OLP.…”
Section: Pros and Cons Of Open-label Placebomentioning
confidence: 99%
“…This can be difficult to navigate, as studies evaluating patient attitudes regarding physician recommendation of placebo have demonstrated that some patients deem it untrustworthy practice, while others feel it is acceptable. [21][22][23] It is generally established, however, that the physician should disclose any information that a reasonable person would want to know and that might influence decision-making; however, there is debate over what exactly this constitutes. In the case of sham surgeries, the physician must communicate the potential risks, but is he or she obligated to explain exactly how the procedure works?…”
Section: Ethical Examination Of Sham Surgeries For Relief Of Chronic mentioning
confidence: 99%